Bridging Gaps in Blood Transfusion Services through Collaborative Healthcare Systems in Cameroon: The Cornerstone University Blood Management System version 1.0 - Lucas Bami Agwe; Emmanuel Bah Afuh Bua; Wilfred Chick Abanda; Didimus Sefela Wirba; Harry Fon Mbacham (International Journal of Blood Transfusion, 2025)
The rising need for structured and efficient blood transfusion services in low-resource settings has driven the adoption of collaborative blood transfusion management systems (CBTMS). This study explores the functionality and impact of the Cornerstone University Blood Management System version 1.0 (CUBMS vs 1.0) in Cameroon. This study was an exploratory research design which used a system interface analysis, comparative case reviews from four countries, and literature synthesis, to reveal that CUBMS improves accessibility, data management, inventory control, emergency responsiveness, and community engagement. Despite infrastructural challenges in rural regions, the system can enhance efficiency, transparency, and safety in blood services. The success of CBTMS in Cameroon is linked to digital infrastructure, training, and culturally relevant community engagement. The Ministry of Public Health of Cameroon should prioritize the nationwide implementation of CBTMS, ensuring consistency in digital health tools.
Keywords: Bridging